Malassezia interaction with a reconstructed human epidermis: Keratinocyte immune response. Issue 10 (29th July 2019) - Pedrosa, Ana F.; Lisboa, Carmen; Branco, Joana; Pellevoisin, Christian; Miranda, Isabel Marcos; Rodrigues, Acacio G.
Summary: The immediate immune response developed by the keratinocytes against Malassezia yeasts has been addressed yielding conflicting results. This study aims the assessment of cytokines and antimicrobial peptides gene expression elicited by M. sympodialis and M. furfur once in contact with a reconstructed human epidermis. A yeast suspension was prepared in RPMI 1640 medium (Sigma‐Aldrich, St. Louis, MO) supplemented with Tween 60 and oleic acid to obtain approximately 1 × 10 6 cells in a volume of 100 μL. Clinical isolates of M. sympodialis (from pityriasis versicolor) and M. furfur (from seborrhoeic dermatitis) were inoculated, separately, onto a reconstructed human epidermis. A distinct expression pattern was found between the two tested species, with a tendency for overexpression of pro‐inflammatory cytokines very soon after infection, whereas no significant expression or gene downregulation was often noticed following 24 and 48 h of incubation. A possible Malassezia species‐dependent immune response pattern is highlighted.